KONTRAK KARYA DAN PERJANJIAN KARYA PENGUSAHAAN PERTAMBANGAN BATUBARA (KK/PKP2B) - Siti Awaliyah (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2014)
The wealth of natural resources in Indonesia tremendous push legislation makers to formulate and adopt legislation that is expected to give birth to prosperity and justice. This research aims to describe the legal basis for contractual arrangements work as one of the agreements relating to mining activities. Works contracts and agreements set works with: (1) Law No. 4 of 2009, (2) Act No.25 of 2007, and (3) of Government Regulation No. 23 of 2010, (4) the Minister of Energy and Mineral Resources No. 1614 of 2004. The procedure for application for a permit contract of work can be done through three pathways based plan which will be the location of the area of ??mining. First, through the Governor-General if the area to be mined are in the two regions of the province. Secondly, through the Governor if the area to be mined are at two district / city different. Asses, a through Regent / Mayor if the area to be mined are at the district / city. In any licensing always involve the President, the Parliament, the Minister of Energy and Mineral Resources, BKPM, Director- General, Governor, Regent / Mayor, the bank and the Applicant.